A life cycle greenhouse gas assessment of remanufactured refrigeration and air conditioning compressors. (30th August 2011) - Biswas, Wahidul; Rosano, Michele
Remanufacturing can importantly reduce the resource intensity and increase the eco-efficiency of product systems by utilising recovered end of life (EOL) parts. A life cycle assessment (LCA) has been carried out to determine the greenhouse gas emissions from the production of a remanufactured compressor vs. a new original equipment manufacturer (OEM) compressor. The remanufacturing consisted of five stages: disassembling, cleaning and washing (C&W), machining, reassembling, and testing. The analysis determined that remanufactured compressors produce about 89% to 93% less greenhouse gas (GHG) emissions than those associated with a new (OEM) compressor and also 50% cheaper than a new (OEM) compressor. The analysis also confirmed that additional reuse and less replacement of parts with new parts can further reduce the overall GHG emissions of remanufactured compressors. The research concludes that remanufacturing can be regarded as a sustainable manufacturing operation that helps attain economic, environmental and social pillars of sustainability.